THE DYNAMICS OF STUDENT ENGAGEMENT, UNIVERSITY IMAGE, AND INSTITUTIONAL SUPPORT IN FOSTERING PRO-ENVIRONMENTAL BEHAVIOUR AMONG SANATA DHARMA UNIVERSITY STUDENTS (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
The study explores the intricate dynamics of student engagement, university image, and institutional support in shaping pro-environmental behaviour among 210 students at Sanata Dharma University. Employing a multiple regression approach and utilizing questionnaires for data collection, the research unveils a significant positive correlation between university support, student participation, and pro-environmental behaviour. Notably, the perceived university reputation appears to exert minimal influence on environmental attitudes and behaviours, challenging initial predictions. These findings emphasize the pivotal roles of student engagement and institutional support, prompting the need for strategic interventions. Tailored approaches should leverage the positive impact of university support and student involvement while recognizing the limited sway of the university's image on pro-environmental attitudes. This study challenges preconceived notions and provides a robust foundation for targeted strategies to foster a sustainable and environmentally conscious campus community at Sanata Dharma University, offering practical insights for cultivating a culture of environmental responsibility.
Keywords: Student Engagement; University Image; Institutional Support; Fostering Pro-Environmental Behavior